Electrochemical sensing of uric acid using bismuth-silver bimetallic nanoparticles modified sensor - Van der Horst, Charlton; Gil, Eric de Souza; Somerset, Vernon (Eclética Química, 2024)
We showcase in this investigation a GCE/Bi–Ag electrochemical nanosensor for uric acid (UA) detection in commercial fruit juice samples. These GCE/Bi–Ag nanosensor electrochemical performances were studied using cyclic voltammetry (CV) and differential pulse voltammetry (DPV) modes showing excellent electrochemical properties toward UA detection in contrast with the clean GCE. Using the fabricated nanosensor, we exploited DPV measurements to detect UA at a meager limit of detection (0.6 μmol/L, S/N = 3) and linearity between 5.0 and 80 μmol/L UA. Furthermore, the GCE/Bi–Ag nanosensor illustrates good repeatability and reproducibility with 3.80% and RSDs of 3.22%, respectively. The GCE/Bi–Ag nanosensor was effectively exploited to determine UA in actual fruit juice samples showing excellent recoveries, indicating that it can be a promising alternative sensor for food analytical applications.